Diacronic and null subject in brazilian portuguese: comparative study (Filologia e Linguística Portuguesa, 2014)
Our goal in this work is to diachronically examine and describe the subject in Brazilian Portuguese (BP), through a comparative study with data from European Portuguese (EP). In order to do so, we have assembled a corpus of Brazilian newspapers – O Recreador Mineiro (1845-1848); O Jornal Mineiro (1897-1900) e Tribuna de Ouro Preto (1945-1948) – and Portuguese newspapers Illustração luzo-brasileira (1856-1858); O Manuelinho de Évora (1890-1898) e Notícias de Évora (1945-1948). More than 14,000 sentences were analyzed to describe the studied phenomena. The quantitative results showed that BP grammar underwent a change with regard to the use of null subjects: it lost the features typical of a consistent null subject language and acquired properties typical of a partial null subject language. We have found out that anaphorical lexical subjects are one of the strategies to realize the subject position in the BP database. A change in the grammar of null subjects in the BP data is observed from their respective numbers when compared to those of EP, which have remained constant, with a high frequency during all periods analyzed according to their syntactic environments. In addition, the EP showed no need to use strategies to fill as was attested in BP. The realization of the null subject with first person presented a different behavior of the null subject of the third person in the BP data, which reinforces the hypothesis that BP be a partial null subject language.